Integrated vertical farming system an innovative way of efficient utilization of small-land and farm resources in urban areas - Singh, A. K.; Das, D. (Indian Farming, 2018)
An integrated approach of rearing animals and poultry along with fodder and daily uses of vegetables and spices gardening was adopted covering an area of 250 sq ft only. The system provides rearing of egg laying poultry, broiler, rabbits and goats. Pot cultures for growing small fodder for rabbits and daily uses of vegetables for household also be integrated. Unemployed youth of urban area can earn up to Rupees 1.85 lakh (net profit) with an annual expenditure of aboutÂ Rupees 1.30 lakh. The construction cost of IVFS is aboutRupees 1.50 lakh which can be recovered within 2 years of operation of Integrated Vertical Farming System.